2022
DOI: 10.5455/medarh.2022.76.72-74
|View full text |Cite
|
Sign up to set email alerts
|

Atypical Presentation of Erythema Nodosum Following Pfizer-BioNTech COVID-19 Vaccine

Abstract: Background: Erythema nodosum (EN) is a common form of panniculitis that could be triggered by numerous conditions including infectious and non-infectious conditions. So far, few cases of EN caused by COVID-19 vaccine had been reported. Case Report: We report a case of atypical presentation of EN mimicking cellulitis in a patient who received the first dose of the Pfizer-BioNTech COVID-19 vaccine. A 38-year-old healthy woman who developed painful swelling on the left leg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 9 publications
0
3
0
Order By: Relevance
“…In one study, a biopsy from a cellulite-like lesion, which did not respond to antibiotics, revealed septal infiltration composed of mixed cells, hemorrhage, and edema in the hypodermis with mild septal fibrosis, which was consistent with drug-induced erythema nodusum. 59…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In one study, a biopsy from a cellulite-like lesion, which did not respond to antibiotics, revealed septal infiltration composed of mixed cells, hemorrhage, and edema in the hypodermis with mild septal fibrosis, which was consistent with drug-induced erythema nodusum. 59…”
Section: Resultsmentioning
confidence: 99%
“…58 In one study, a biopsy from a cellulite-like lesion, which did not respond to antibiotics, revealed septal infiltration composed of mixed cells, hemorrhage, and edema in the hypodermis with mild septal fibrosis, which was consistent with drug-induced erythema nodusum. 59 In a case series of 58 patients, postvaccine reactions had been categorized as vaccine-related papules and plaques (V-REPP), which showed a spectrum of spongiosis and interface changes in microscopy. 60 Perino/Chilblain-like Acral Pattern Histopathologic assessment on post-COVID vaccination chilblain-like lesions presented with superficial and deep dermal inflammatory infiltrates surrounding vessels, sweat glands, and occasionally nerves.…”
Section: Urticaria and Angioedemamentioning
confidence: 99%
“…Of the 405 skin reactions reported following COVID-19 vaccination (within 21 days after vaccination) via a questionnaire survey in Spain, the COVID arm accounted for 32.1%; however, EN was not reported as a COVID-19 vaccination-induced skin reaction. 7 Table 1 presents 18 case reports regarding EN following COVID-19 vaccination, [2][3][4][5][6][8][9][10][11][12][13][14][15][16][17][18] which mostly develops on the extremities (especially the lower limbs) of adult women and improves within 1 month. These features are similar to those of common (irrelevant to COVID-19 vaccination) EN.…”
Section: Discussionmentioning
confidence: 99%